Hydrogen purification from binary syngas by PSA with pressure equalization using microporous palm kernel shell activated carbon. (1st October 2019) - Shamsudin, I.K.; Abdullah, A.; Idris, I.; Gobi, S.; Othman, M.R.
Abstract: Hydrogen (H2 ) produced from fossil sources via steam reforming of natural gas requires further purification before it can be safely used for human consumption and as fuel to generate electricity from hydrogen fuel cells. A promising technology for H2 purification from carbon dioxide (CO2 ) is by pressure swing adsorption (PSA) using palm kernel shell activated carbon. The adsorbent exhibited higher affinity for CO2 than H2 . The adsorption system was capable of achieving H2 purity of almost 100% with H2 recovery of 88.43%. H2 contributed 6.62 J.min −1 of the energy requirement from the total energy of 6.63 J.min −1 as a result of pressurization of the gas at 3 bar. H2 contributed 5.85 J.min −1 energy from depressurization of the gas to 1.5 bar. The modest energy requirement with high level of H2 purity and recovery demonstrated the effectiveness of PSA with pressure equalization mode for H2 purification from syngas.